Bentuk ekspresi emosi kata dan emoji berdasarkan gender dalam media sosial dari perspektif linguistik - Norwati, Mohd Zain (2021)
The dynamism of textual content in digital technology has shaped an unpredictable lifestyle of the cyber community. Furthermore, the existence of Facebook as a network platform which easily accessible, user friendly and available for free has become a field for digital information sharing in public. The unique relationship between languages, emotions and genders in the cyber world has indirectly sparked a new phenomenon that needs to be re-examined by contemporary scholars. The findings from previous critical analysis of the literature demonstrate that studies regarding emotional expressions had been explored but separately through disciplines such as linguistics or psychology. Although there is a lot of research vis-à-vis emotional expressions of gender, none have focused on the emotional expressions of digital texts in the cyber world. Even if there are available research on emotional expressions, the scope might not directed towards the form of emotional expressions in words and expressions in emojis in the cyber world. Thus, this study aimes to compare the form of emotional expressions of gender for both males and females on Facebook (Fb) and to describe the language phenomenon which highlights the form emotional expressions of the male and female ganders on Fb. The study was grounded on discipline of semantics with the application of Corpus Linguistics and reinforced by the Constructed Emotion Theory (CAT). The research data in the form of digital texts, were collected from selected respondents via Cyber Advertising Method (CAM). The emotional expressions of words were analysed using the AntConc 3.5.2 software and the American Standard Code II (ASCII) was used to analyse the expressions of emojis. A total amount of 5,683,637 tokens, 804,280 types and 948,290 emojis were collected and analysed in the study. Four linguistic phenomena were observed namely the emotional expressions of the words [fear] for males and females; the emotional expressions of the word [anger] for males and females; the emotional expressions representing the emotions of male and female; and the emotional expressions in emojis that accompanies the form of emotional expressions of words for males and females. To conclude, the research findings were able to scientifically described the linguistic phenomena which highlights the form of emotional expressions of words and emojis based on gender in Fb via a systematic and empirical research method.